Detection of Cryptosporidium sp infection by PCR and modified acid fast staining from potassium dichromate preserved stool (Medical Journal of Indonesia, 2009)
Aim: To identify the frequency of Cryptosporidium infection in children below 3 years old by examining concentrated long term preserved stool using PCR detection of 18S rRNA gene and compared with modified acid fast staining technique. Methods: Hundred eighty eight stools from children ≤ 3 years old were stored for 13 months in 2.5% K2Cr2O7 solution at 40 C. Cryptosporidium oocysts were isolated by water-ether concentration technique. The concentrates were smeared onto object glass and stained with modified acid fast staining, and the rest of the concentrates were DNA extracted by freezing and thawing cycles and proteinase K digestion, then direct PCR was done to detect 18S rRNA gene. Result: The proportion of positive stools for Cryptosporidium sp by acid fast staining from concentrated stools and 18S rRNA PCR were 4.8% and 34.6% respectively, which showed statistically significant difference. Conclusion: The frequency of Cryptosporidium infection among children ≤ 3 years old was very high and stool storage in K2Cr2O7 for 13 months did not affect the PCR result. High prevalence of Cryptosporidium infection indicated high transmission in that area and the potential to be transmitted to other individuals such as the immunocompromised. (Med J Indones 2009;18:147-52)